A Qualitative Study of the Sportive Performance Levels of Elite and Amateur Athletes in the Covid 19 Process - Ender Özbek; Hüseyin Nasip Özaltaş; Sıtkı Özbek (Türk Spor ve Egzersiz Dergisi)
COVID-19 affected the whole world and affected the sports circles negatively as in many areas of life. While sports federations and sports circles focused on managing the process with effective solutions, they had to give a new direction to their work by having to continue their training at home in order not to reduce their performance levels, which are elite and amateur who continue to do sports and do sports at high performance levels. In this context, this research was carried out to collect and examine information about the developing training processes that elite and amateur athletes had to carry out their own researches at home due to the COVID-19 epidemic and their efforts to maintain their performance levels. 6 elite and 6 amateur athletes from different branches voluntarily participated in the study. In the study, interviews were conducted, one of the qualitative methods. A structured interview form was used as a data collection tool. It was used for descriptive analysis in the analysis of the data. In our descriptive analysis, now, in our research, the efforts of elite athletes and amateur athletes to protect the performance levels of Cov-19 quarantine athletes and the training to overcome the difficulties they encounter, the emerging difference is where the club approach is where the club approach, the surrounding approach and the social media approach are professional and amateur athletes look at the emerging problems from the same window and meet a difference in their individual theme.